Chromogranin A Expression in Rectal Neuroendocrine Tumors Is Associated With More Aggressive Clinical Behavior and a Poorer Prognosis. (November 2020) - Kim, Jisup; Kim, Joo Young; Oh, Eun Hye; Yoo, Changhoon; Park, In Ja; Yang, Dong-Hoon; Ryoo, Baek-Yeol; Ryu, Jin-Sook; Hong, Seung-Mo
Abstract : Although rectal neuroendocrine tumors (NETs) with an L-cell phenotype and small size are generally less clinically serious, the new 2019 World Health Organization (WHO) classification system has categorized all of these lesions as malignant. Identifying biomarkers of rectal NETs is thus important for stratifying their clinical behavior. Chromogranin A protein expression was assessed in 538 endoscopically or surgically resected rectal NETs and compared with clinicopathologic factors to identify its clinical and prognostic significance. All of the rectal NETs analyzed (100%) were synaptophysin positive, but chromogranin A labeling was only detected in 111 cases (20.6%). Chromogranin A expression in the rectal NETs was more commonly associated with older age (50 y and older; P =0.013), male sex ( P =0.002), radical resection ( P =0.003), large tumor size (≥1 cm; P =0.038), muscularis propria invasion ( P =0.002), lymphovascular ( P =0.014) and perineural ( P <0.001) invasion, an involved resection margin ( P =0.028), and lymph node metastasis ( P =0.003). Patients with chromogranin A expression had higher plasma chromogranin A levels ( P =0.023) than those without chromogranin A expression during follow-up. The 10-year disease-free survival rate in rectal NET patients with chromogranin A expression (91.5%) was significantly shorter than the negative cases (99.7%) by both univariate (hazard ratio=14.438; 95% confidence interval: 2.911-71.598; P <0.001) and multivariate (hazard ratio=12.099; 95% confidence interval, 2.044-71.608; P =0.006) analyses. In summary, rectal NETs that are positive for chromogranin A are less common than those with synaptophysin expression and show more aggressive clinical behavior. Chromogranin A is therefore a prognostic indicator of higher recurrence risk in patients with endoscopically or surgically resected rectal NETs.